2018
DOI: 10.1103/physreva.98.062705
|View full text |Cite
|
Sign up to set email alerts
|

Few-body states of bosons interacting with a heavy quantum impurity

Abstract: We consider the problem of a fixed impurity coupled to a small number N of non-interacting bosons. We focus on impurity-boson interactions that are mediated by a closed-channel molecule, as is the case for tuneable interatomic interactions in cold-atom experiments. We show that this two-channel model can be mapped to a boson model with effective boson-boson repulsion, which enables us to solve the three-body (N = 2) problem analytically and determine the trimer energy for impurity-boson scattering lengths a > … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(20 citation statements)
references
References 49 publications
1
19
0
Order By: Relevance
“…Our findings complement recent theory predictions for localized impurities in a Bose gas, where it was found that the impurity induces a strong boson-boson repulsion even in the absence of any direct repulsive interaction [69,70]. Therefore, a picture is emerging where the ground state of the Bose polaron with short range interactions appears well described by calculations including only a few excitations of the medium.…”
Section: Discussionsupporting
confidence: 88%
“…Our findings complement recent theory predictions for localized impurities in a Bose gas, where it was found that the impurity induces a strong boson-boson repulsion even in the absence of any direct repulsive interaction [69,70]. Therefore, a picture is emerging where the ground state of the Bose polaron with short range interactions appears well described by calculations including only a few excitations of the medium.…”
Section: Discussionsupporting
confidence: 88%
“…The κ ≪ 1 regime was recently investigated in Refs. [31,32]. Our goal is to describe four-and higher-body states that are universally linked to BBX Efimov trimers.…”
Section: A System Hamiltonianmentioning
confidence: 99%
“…For two-component systems, comparatively little is known about N -body states tied to Efimov trimers [11,12,[24][25][26][27][28][29][30][31][32]. Assuming that the impurity and the bosons have the same mass but are distinguishable, the fourbody system has been found to display characteristics that are similar to the single-component case [12].…”
Section: Introductionmentioning
confidence: 99%
“…We present the explicit form of the wave functions ζ λp and η λ in Ref. [16]. The states B † λ |0 form an orthonormal basis of the twobody Hilbert space, and thus B λ satisfies bosonic commutation relations.…”
Section: Motivated By the Above We Tackle This Problem By Ex-mentioning
confidence: 99%
“…Second, although we have introduced an extra interaction term, it has the form of a separable potential. The separability of the interaction significantly simplifies the calculation of few-body properties and allows us to derive a series of analytical results [16], which we now discuss. Trimer and tetramer energies (solid) for the twochannel model measured from the dimer energy as a function of |r0|/a.…”
Section: Motivated By the Above We Tackle This Problem By Ex-mentioning
confidence: 99%